Experimental and numerical investigations on flexural behaviour of CFRP reinforced concrete-filled stainless steel CHS tubes. (1st February 2018) - Feng, Ran; Chen, Yu; Wei, Jiangang; Huang, Jinyan; Huang, Junfei; He, Kang
Highlights: CFRP reinforced concrete-filled stainless steel CHS beams were investigated. Strengthening effect of CFRP was improved with the increase of the strength ratio of CFRP. Enhancement of the ultimate strength was increased with more layers of CFRP. Enhancement of the strength is generally decreased with the increase of the thickness of CFRP reinforced CFST tubes. Abstract: An experimental investigation was conducted on CFRP reinforced concrete-filled stainless steel circular hollow section (CHS) tubes subjected to in-plane bending. A total of 36 specimens including concrete-filled stainless steel CHS tubes and CFRP reinforced concrete-filled stainless steel CHS tubes were tested. An extensive parametric study was carried out by using the verified finite element model to investigate the strengthening effect of CFRP on the flexural behaviour of concrete-filled stainless steel CHS tubes. It is shown from the comparison that the strengthening effect of CFRP improved with the increase of the strength ratio ( β ) of CFRP. Furthermore, the ultimate strength was enhanced proportionally with the increase of the layers of CFRP positioned in the longitudinal direction for reinforcement, but the ductility generally deteriorated. Finally, the flexural strength and flexural stiffness of concrete-filled stainless steel CHS tubes is improved by increasing the interface friction coefficient between stainless steel tubes and concrete up to 0.6.